10. CURRENT STATUS OF DISEASE STRUCTURE OF INPATIENTS TREATED AT THE VIETNAM NATIONAL EYE HOSPITAL IN THE PERIOD OF 2019-2022 (Vietnam Journal of Community Medicine, 2023)
Objective: Describe the current status of the disease structure of inpatients at the Central Eye Hospital from 2019 to 2022. Method: A cross-sectional descriptive retrospective study. All medical records of patients hospitalized for inpatient treatment at the National Eye Hospital from January 1, 2019 to December 31, 2022, saw a total of 111,601 qualified medical records used in the study. Result: The gender ratio was 0.85:1. Most patients who come to the Vietnam National Eye Hospital for inpatient treatment are over 60 years old. More than 80% of patients admitted to the hospital had health insurance. The proportion of patients entering the on-demand medical examination department has the highest percentage among hospital admissions through the inpatient departments. Meanwhile, the lowest belongs to the patients entering the cosmetic department. The number of inpatients, divided into months in a year, mostly are hospitalized from March to July. In the proportion of patients admitted to inpatient treatment according to ICD-10 classification, the majority of subjects hospitalized due to cataracts accounted for 44.65% in 4 years. About 98% of the subjects were discharged from the hospital in a state of cure/recovery in 2019-2022. Conclusion: In the last 4 years, from 2019 to 2022, there were a total of 111,601 inpatients admitted to the National Eye Hospital, mainly due to cataracts disease.
Keywords: Disease structure, eye, period 2019-2022.